Rompendo o labirinto do esquecimento: redes de poder e emancipação feminina em Tia Dodô da Portela - Angélica Ferrarez de Almeida (Les Cahiers ALHIM)
Searching the labyrinths of oblivion is an opportunity to rewrite the stories of black women in the first person, since in the selection of what one wants to remember, the work and trajectory of black subjects and subjects in history went through a project of intentional erasure of knowledge and practices of groups called subordinates. The dismantling of this project is urgent in countries considered to be the periphery of the world, since the limitations of this system ended up imploding it, causing insurgent voices of black women to seek the (re) assembly of a society, in fact, developed. In Brazil, the confrontation with a country deep in contradictions, has created space for the expansion of the internationalist struggle of women, and, in this sense, I have been reflecting how the protagonists of samba manage to create networks of power that aim at the emancipation of an entire community. A good example is in the Tia Dodô da Portela flag-bearer, and it is through it that we will analyze deep militancy strategies developed by black women in the field of knowledge, spaces and memory.